Tuning work function and surface-modified AZO films on FTO substrate to improve the efficiency of thin-film silicon solar cells - Park, Hyeong Gi; Lee, Jae Hyun; Yi, Junsin (Journal of Materials Science: Materials in Electronics, 2023)
Light trapping plays a critical role in improving the current density of thin-film silicon solar cells. However, commercial fluorine-doped tin oxide (FTO) substrates have limitations in enhancing current density in a specific wavelength range due to weak haze values in the long wavelength range, particularly for amorphous or microcrystalline silicon absorber layers. This problem may be caused by damage from hydrogen plasma during the deposition of hydrogenated silicon. To address this issue, a sputtered AZO film is used as a protective layer on the FTO substrate, enhancing light scattering in the near-infrared region. After optimizing the target angle (47.5 degrees) and thickness (60.9 nm) of the AZO film, thin-film silicon solar cells based on an amorphous silicon layer achieved a current density of 15.31 mA/cm2 compared to 14.22 mA/cm2 for the FTO substrate. The efficiency also improved to 9.63% as the fill factor increased to 70.62%.
Keywords: Absorber layers; AZO films; Fluorine doped-tin oxides; Light-trapping; Long-wavelength-range; Oxide substrates; Silicon absorbers; Surface-modified; Thin-film silicon solar cells; Wavelength ranges